FINANCIAL LITERACY AMONG MUSLIM UNIVERSITY STUDENTS - Wan Noor Hazlina Wan Jusoh,; Siti Nur Hidayah Mohd Yusdi, (Journal of Islamic, Social, Economics and Development, 2022)
As a university student, it is crucial to have enough knowledge regarding financial management to allow them to react competently to life events in the future. Nowadays, the concerns of students with financial problems are worrying. With the amount of the loan or scholarship obtained, many students still struggled to handle their money adequately. Therefore, this research paper aims at examining the level of financial literacy among Muslim University students at Universiti Teknologi MARA Cawangan Terengganu (UiTMCT), Dungun Campus. The researcher distributed an online questionnaire to students in UiTMCT Dungun Campus using convenience sampling and collected 204 of them. The results revealed that the financial literacy level among Muslim University students at UiTMCT Dungun Campus is high that contradicts with what have been reported by previous studies due to imbalanced number of participants.